Odpowiedzi

  • Użytkownik Zadane
2010-01-06T17:04:48+01:00
- 0,2 (-b -1) =
0,2b+0,2=0 //*10
2b+2=0
2b=-2
b=-1
- (4x + 3 - 1/2y) =-4x-3+1/2y
-5 (-3a +b - 0,7) =15a-5b+3,5
- (-1/2t - z 6) =1/2t+z6


(2x + 8) : (-2) =-x-4
(a - 10) : 5 =a/5 - 2
9x - 7y - 3 / 3 =3x-7/3y-1
(-4z - 2t) : 1/2 =-2z -t
(4w - 2 + 3 u) : (-1 1/3) =(4w-2+3u)*(-3/4)=-3w+3/2-9/4u
0,6x + 10y - 1 / -0,2 =-0,3x-5y+5
2010-01-06T17:07:35+01:00
Rozwiązania:
a) - 0,2 (-b -1) =0,2b+0,2
b)- (4x + 3 - 1/2y) =-4x-3+1/2y=-4x-2+1/2y
c)-5 (-3a +b - 0,7) = 15a-5b+3,5
d)- (-1/2t - z 6) =-1/2t+z 6

pierwsza czesc ;D